Massage with Chinese herbal medicine compound ointment combined with Traditional Chinese Medicine hot compress in the treatment of urinary retention after operation for mixed hemorrhoids and related nursing measures: A care report (中药膏摩联合中药热奄包治疗混合痔术后尿潴留1例的护理体会) - QIN Shasha (秦沙沙); DONG Yuxia (董玉霞); ZHANG Jing (张敬); LI Ye (李野); E Haiyan (鄂海燕); WEI Yongchun (魏永春) (Association of Integrative Nursing, 2021)
This paper summarized the nursing experience of a patient who received massage with Chinese herbal medicine compound ointment combined with Traditional Chinese Medicine (TCM)hot compress in the treatment of urinary retention after operation for mixed hemorrhoids. The degree of urinary retention was evaluated according to the TCM symptom integral, and massage with Chinese herbal medicine compound ointment combined with TCM hot compress therapy was carried out to improve the urination function and reduce the pain. (本文总结1例中药膏摩联合中药热奄包治疗混合痔术后的护理体会。根据该例患者排尿症状积分标准进行评估, 通过实施腹部中药膏摩联合中药热奄包治疗, 明显改善患者尿潴留的症状, 减轻了患者的痛苦。)